Fashion and History of Dresses applied in the study of museology. (ModaPalavra e-periódico, 2012)
The article discusses the work of museology having as a source of analysis and observation modes and fashions captured by photographs from family albums and or history of dresses of the time, especially in like memory and the look on social practices contribute to the study of clothing, having as vehicle research and dissemination in a virtual museum. This approach is directly related to the work of the research group - Museum of clothes and fashion (MIMO) - Postgraduate program in Design at the University Anhembi Morumbi.
Keywords: Design; Fashion; Museum